The effect of the Theo van Gogh murder on house prices in Amsterdam - Pieter A. Gautier; Arjen Siegmann; Aico van Vuuren (Institute for the Study of Labor (IZA), 2007)
This paper estimates the impact of the murder of film maker Theo van Gogh on November 2, 2004, on listed house prices in Amsterdam with a unique dataset. We use an hedonic-market approach to show that general attitudes towards Muslim minorities were negatively affected by the murder. Specifically, we test for an effect on listed house prices in neighborhoods where more than 25% of the people belong to an ethnic minority from a Muslim country (type I). Relative to the other neighborhoods, house prices in type I neighborhoods decreased in 10 months by about average 3%, with a widening gap over time. The results are robust to several adjustments including changes in the control group. There is no significant difference in the time it takes for houses to be sold in type I versus other neighborhoods. Finally, people belonging to the Muslim minority were more likely to buy and less likely to sell a house in a type I neighborhood after the murder than before.
urn:nbn:de:101:1-20080425150
Keywords: 330; Innere Sicherheit; Politische Gewalt; Islamisch; Immobilienpreis; Amsterdam